Synthesis of L-asparagine Catalyzed by a Novel Asparagine Synthase Coupled With an ATP Regeneration System - Luo, Wei; Xu, Jinglong; Chen, Huiying; Zhang, Huili; Yang, Peilong; Yu, Xiaobin (Frontiers in Bioengineering and Biotechnology, 2021)
Compared with low yield of plant extraction and environment incompatibility of chemical synthesis, biocatalysis by asparagine synthetase (AS) for preparation of L-asparagine (L-Asn) has become a potential synthetic method. However, low enzymatic activity of AS and high cost of ATP in this reaction restricts the large-scale preparation of L-Asn by biocatalysis. In this study, gene mining strategy was used to search for novel AS with high enzymatic activity by expressing them in Escherichia coli or Bacillus subtilis. The obtained LsaAS-A was determined for its enzymatic properties and used for subsequent preparation of L-Asn. In order to reduce the use of ATP, a class III polyphosphate kinase 2 from Deinococcus ficus (DfiPPK2-Ⅲ) was cloned and expressed in E. coli for ATP regeneration. A coupling reaction system including whole cells expressing LsaAS-A and DfiPPK2-Ⅲ was constructed to prepare L-Asn from L-aspartic acid (L-Asp). Batch catalytic experiments showed that sodium hexametaphosphate (>60 mmol•L-1) and L-Asp (>100 mmol•L-1) could inhibit the synthesis of L-Asn. Under fed-batch mode, L-Asn yield reached 90.15% with twice feeding of sodium hexametaphosphate. A final concentration of 218.26 mmol•L-1 L-Asn with a yield of 64.19% was obtained when L-Asp and sodium hexametaphosphate were fed simultaneously.